Evaluation of building analysis approaches as a basis for the energy improvement of city districts - Zoe Mayer; Rebekka Volk; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2021)
Municipalities in Germany develop policy plans referred to as 'Energetische Quartierskonzepte' (EQ, pl. EQs) to lower and decarbonize the energy consumption of existing buildings in whole city districts. These EQs describe the status-quo, a strategy, and measures for the energy-related improvement of a district based on an initial analysis of the buildings in the considered area. We study 25 publicly available reports of German EQs to identify common state-of-the-art approaches for the analysis of buildings on district scale, summarizing their strengths and weaknesses. We extract ten approaches that are currently applied in practice. Overall, we could not find any connection between the year of the EQ publication, the district size, and the type and quantity of analysis approaches used. The most common approaches for obtaining data for building analyses are the use of representative building typologies, on-site inspections of buildings, datasets from network-operators, and citizen surveys. The main weaknesses of the assessed approaches are for example inaccuracies due to simplifying assumptions, inconsistent data formats from different data sources, and problems due to data protection restrictions. The standardization, combination, and further development of the assessed approaches are recommended.
Keywords: 330; heating; building retrofits; urban transition; district analysis; building inspection; neighborhood